Literatur Review : Tren Penggunaan Aplikasi Sebagai Fasilitator Dalam Penerapan Model Blended Learning Pada Pembelajaran Fisika - Islami, Anggun Variasi; Sunni, M. Abdurrahman (JUPE : Jurnal Pendidikan Mandala, 2023)
This study aims to see what applications are commonly used by teachers in teaching physics with blended learning. This study uses a literature review method. from the search results retrieved four articles that represent the use of the application as a facilitator in applying the blended learning model to learning physics. The applications used in the articles that were successfully reviewed were the Zoom Meeting, Whatapp, PHeT simulation, Quipper School, and Edomo applications. Based on the review results, it was found that each application has its own advantages. but both are able to improve learning outcomes and student independence in learning. Especially for the PHet simulation application, students who have low abilities have lower scores when using blended learning assisted by the PHet simulation. Whereas students who have high abilities have higher scores when using the PHeT simulation. This is because each student requires proficiency in using technology, availability of facilities and sufficient ability or understanding to maximize the potential of the media PhET simulation